Behavioral Health Risk and Resilience among International Students in the United States: A Study of Socio-demographic Differences - Kim, Youn Kyoung; Maleku, Arati; Lemieux, Catherine M; Du, Xi; Chen, Zibei (Journal of International Students, 2019)
Using a resilience framework, the current cross-sectional study examined indicators of behavioral health risk and resilience among U.S. international students (N=322) across key socio-demographic characteristics. A multimethod approach was used to collect data with both an online platform and paper-based survey instrument. Results showed that higher levels of acculturative stress were reported by older students, females, undergraduates, students who lived with their families, and those who had resided in the US longer than 2 years. Findings underscore the importance of culturally-relevant screening and prevention strategies that target resilience and other protective factors to reduce health risk and encourage well-being and academic success among international students.